Rootstocks as factors influencing the fruit quality and antioxidant activityof ‘Grace Star’ sweet cherry - Tomo Milošević; Nebojša Milošević; Nemanja Miletić; Radmila Ilić (Journal für Kulturpflanzen)
The effect of 14 rootstocks on fruit quality and antioxidant potential of ‘Grace Star’ sweet cherry was studied during 5th and 6th year after planting. The experiment was performed in the Prislonica vilage (Čačak, Serbia), on a heavy, shallow and acidic soil. The results showed that rootstocks had a significant effect on all tested properties. Apart from them, a significant influence, with some exceptions, was exerted by year alone and interaction rootstock × year. With regard rootstocks, ‘Cigančica’ and Myrobalan seedlings simultaneously and ‘Cigančica’ alone induced the highest FW, SW, W, T and Dg respectively, whereas ‘Oblačinska’, Krymsk 6, Adara and Myrobalan caused the highest FRa values. Myrobalan promoted the best L and Mahaleb the highest φ and RI; fruits from PHL-A contained the highest TAc, TPC and TFC. Gisela 6 promoted the weakest antioxidant activity, whereas the best was observed in fruits from PHL-C and ‘Cigančica’. The SSC was the highest in fruit from trees grafted on Mahaleb, Colt, PHL-A, Gisela 5 and ‘Oblačinska’, whereas PHL-C induced the lowest. The highest TA was recorded on Adara and Myrobalan with no significant differences between them, and the lowest on Mahaleb, PHL-C and ‘Oblačinska’ also without differences between them. Cherries of trees grafted on invigorating Mazzard and Mahaleb and semi-dwarfing PHL-A showed the highest ash content whereas the lowest was observed on Gisela 6. The PHL-A tended to induce the lowest FW, FRa, fruit dimensions, its size and SL; Adara induced the lowest φ value and pH juice, whereas ‘Cigančica’, Myrobalan and Adara caused similar and the lowest RI values. Regarding years, higher FW, SL, SSC, TA, ash content, TPC and TFC was observed in second year, whereas fruit dimensions, Dg, φ and pH juice was higher in first year of trial. There were significant correlations between TPC, TFC and antioxidant activity, as well as between the TAc and antioxidant activity. Finally, more vigorous rootstocks and less yielding rootstocks improved fruit physical attributes, whereas less vigorous rootstocks increased fruit chemical properties.